Smart cities: global overview of disaster resilience (Research, Society and Development, 2022)
According to the United Nations Organization (UNO), there have been 7,348 disasters worldwide in the last two decades, with 1.23 million people killed, approximately 60,000 people annually. More than 4 billion people have been affected by disasters. Disasters are severe natural phenomena, strongly influenced by regional characteristics, such as rock, soil, topography, vegetation, and also weather conditions. The present paper aims to portray the panorama of disaster resilience worldwide and the importance of cities becoming smart for disaster mitigation and sustainable development. The research will be of exploratory and qualitative nature and used as methodology the review of national and international literature, scientific articles, national and international agencies, dissertations theses for a comprehensive study of the subject. The occurrence of these phenomena in places of human habitation results in several material and human damages, in addition to enormous socio-economic losses, and its correct management for their mitigation is essential. With this, it is necessary the importance in the preparation of nations, better adherence to solve these global problems, urgent actions for the management of risk factors in order to preserve life and the environment for future generations.